Antitumor activity of phenethyl isothiocyanate in HER2-positive breast cancer models - Gupta, Parul; Srivastava, Sanjay K (BMC medicine, 2012)
Background HER2 is an oncogene, expression of which leads to poor prognosis in 30% of breast cancer patients. Although trastuzumab is apparently an effective therapy against HER2-positive tumors, its systemic toxicity and resistance in the majority of patients restricts its applicability. In this study we evaluated the effects of phenethyl isothiocyanate (PEITC) in HER2-positive breast cancer cells. Methods MDA-MB-231 and MCF-7 breast cancer cells stably transfected with HER2 (high HER2 (HH)) were used in this study. The effect of PEITC was evaluated using cytotoxicity and apoptosis assay in these syngeneic cells. Western blotting was used to delineate HER2 signaling. SCID/NOD mice were implanted with MDA-MB-231 (HH) xenografts. Results Our results show that treatment of MDA-MB-231 and MCF-7 cells with varying concentrations of PEITC for 24 h extensively reduced the survival of the cells with a 50% inhibitory concentration (IC 50 ) of 8 μM in MDA-MB-231 and 14 μM in MCF-7 cells. PEITC treatment substantially decreased the expression of HER2, epidermal growth factor receptor (EGFR) and phosphorylation of signal transducer and activator of transcription 3 (STAT3) at Tyr-705. The expression of BCL-2-associated × (BAX) and BIM proteins were increased, whereas the levels of B cell lymphoma-extra large (BCL-XL) and X-linked inhibitor of apoptosis protein (XIAP) were significantly decreased in both the cell lines in response to PEITC treatment. Substantial cleavage of caspase 3 and poly-ADP ribose polymerase (PARP) were associated with PEITC-mediated apoptosis in MDA-MB-231 and MCF-7 cells. Notably, transient silencing of HER2 decreased and overexpressing HER2 increased the effects of PEITC. Furthermore, reactive oxygen species (ROS) generation, mitochondrial depolarization and apoptosis by PEITC treatment were much higher in breast cancer cells expressing higher levels of HER2 (HH) as compared to parent cell lines. The IC 50 of PEITC following 24 h of treatment was reduced remarkably to 5 μM in MDA-MB-231 (HH) and 4 μM in MCF-7 (HH) cells, stably overexpressing HER2. Oral administration of 12 μM PEITC significantly suppressed the growth of breast tumor xenografts in SCID/NOD mice. In agreement with our in vitro results, tumors from PEITC-treated mice demonstrated reduced HER2, EGFR and STAT3 expression and increased apoptosis as revealed by cleavage of caspase 3 and PARP. In addition our results show that PEITC can enhance the efficacy of doxorubicin. Conclusions Our results show a unique specificity of PEITC in inducing apoptosis in HER2-expressing tumor cells in vitro and in vivo and enhancing the effects of doxorubicin. This unique specificity of PEITC offers promise to a subset of breast cancer patients overexpressing HER2.